A robust partial least squares approach for function-on-function regression - BEYAZTAŞ, UFUK (My University, 2022)
The function-on-function linear regression model in which the response and predictors consist of random curves has become a general framework to investigate the relationship between the functional response and functional predictors. Existing methods to estimate the model parameters may be sensitive to outlying observations, common in empirical applications. In addition, these methods may be severely affected by such observations, leading to undesirable estimation and prediction results. A robust estimation method, based on iteratively reweighted simple partial least squares, is introduced to improve the prediction accuracy of the function-on-function linear regression model in the presence of outliers. The performance of the proposed method is based on the number of partial least squares components used to estimate the function-on-function linear regression model. Thus, the optimum number of components is determined via a data-driven error criterion. The finite-sample performance of the proposed method is investigated via several Monte Carlo experiments and an empirical data analysis. In addition, a nonparametric bootstrap method is applied to construct pointwise prediction intervals for the response function. The results are compared with some of the existing methods to illustrate the improvement potentially gained by the proposed method.
Keywords: İSTATİSTİK & OLASILIK; Matematik; Temel Bilimler (SCI); STATISTICS & PROBABILITY; MATHEMATICS; Natural Sciences (SCI); İstatistik ve Olasılık; Analiz; Cebir ve Sayı Teorisi; Matematik (çeşitli); Genel Matematik; İstatistik, Olasılık ve Belirsizlik; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Statistics and Probability; Analysis; Algebra and Number Theory; Mathematics (miscellaneous); General Mathematics; Statistics, Probability and Uncertainty; Physical Sciences; Social Sciences & Humanities